Jamides wananga, a new species from Papua New Guinea and Australia (Lepidoptera: Lycaenidae) - Wilson, Peter R.; Johnson, Ian R.; Lohman, David J. (Zootaxa, 2021)
Jamides wananga sp. n. is described and illustrated from Madang Province of Papua New Guinea and Dauan Island in the Torres Strait (Queensland, Australia). The new species is similar in appearance to several other Jamides Hübner species in the bochus-group. DNA sequence data and morphology were used to distinguish the nominotypical subspecies found on the New Guinea mainland from J. w. roxina subsp. n. on Dauan Island. Notes on the habitat and behaviour are also provided.